Contested Memories in Chinese and Japanese Foreign Policy - Dian, Matteo (Chandos Publishing, 2017)
Contested Memories in Chinese and Japanese Foreign Policy explores the issue of memory and lack of reconciliation in East Asia. As main East Asian nations have never achieved a common memory of their pasts, in particular, the events of the Second World War and Sino-Japanese War, this book locates the issue of memory within International Relations theory, exploring the theoretical and practical link between the construction of a country’s identity and the formation and contestation of its historical memory and foreign policy.Provides an innovative theoretical frameworkDraws connections between the role of memory and foreign policyUses the interpretative theory of international relationsGives comparative perspective using the cases of China and JapanPresents in-depth analysis of the construction and contestation of national memory in China and Japan
Keywords: References - Boel et al. (2021); Archives and Human Rights

News from the ICA Human Rights Working Group - 2017-10 (October) - Peterson, Trudy Huskamp (ICA, 2017)
Keywords: Oct'17 newsletter link to Nov'17.